Pengemasan Seni Tradisi Jaranan Turonggo Yakso Di Sanggar Purwo Budoyo Trenggalek - Vitaloka, Frenita Aniss; Pratamawati, Endang Wara Suprihatin Dyah; Istiandini, Winda (Mahesa Research Center, 2025)
The reason the researcher chose Sanggar Purwo Budoyo is because the studio has packaged the traditional art of Jaranan Turonggo Yakso in Dongko District, Trenggalek Regency. The purpose of this study is to describe the Jaranan Turonggo Yakso Packaging Process by Sanggar Purwo Budoyo. The research method uses descriptive qualitative with data collection through interviews, observations, and documentation studies. Data verification uses source triangulation and technique triangulation. The results of this study, namely the first discussion through pre-packaging concerning the initial design to the end of activities in a production, the second discussion is packaging regarding shooting and editing activities, in the packaging process it is very complicated, the third stage is post-packaging which goes through the stages of the shooting results carried out for (editing) is a final process of production. Conclusions are made systematically to ensure good and attractive product quality. This stage includes content preparation, label and cover creation, labeling, cover installation, quality control, to final packaging. Suggestions for using more attractive label and cover designs, reflecting the identity of local arts and culture, with striking yet aesthetic color and font elements, add interesting information such as a short description of Jaranan Turonggo Yakso or a short profile of the studio.